Inactivation of Carbonyl-Detoxifying Enzymes by H2O2 Is a Trigger to Increase Carbonyl Load for Initiating Programmed Cell Death in Plants - Md. Sanaullah Biswas; Ryota Terada; Jun'ichi Mano (MDPI AG, 2020)
H2O2-induced programmed cell death (PCD) of tobacco Bright Yellow-2 (BY-2) cells is mediated by reactive carbonyl species (RCS), degradation products of lipid peroxides, which activate caspase-3-like protease (C3LP). Here, we investigated the mechanism of RCS accumulation in the H2O2-induced PCD of BY-2 cells. The following biochemical changes were observed in 10-min response to a lethal dose (1.0 mM) of H2O2, but they did not occur in a sublethal dose (0.5 mM) of H2O2. (1) The C3LP activity was increased twofold. (2) The intracellular levels of RCS, i.e., 4-hydroxy-(E)-hexenal and 4-hydroxy-(E)-nonenal (HNE), were increased 1.2−1.5-fold. (3) The activity of a reduced nicotinamide adenine dinucleotide phosphate (NADPH)-dependent carbonyl reductase, scavenging HNE, and n-hexanal was decreased. Specifically, these are the earliest events leading to PCD. The proteasome inhibitor MG132 suppressed the H2O2-induced PCD, indicating that the C3LP activity of the β1 subunit of the 20S proteasome was responsible for PCD. The addition of H2O2 to cell-free protein extract inactivated the carbonyl reductase. Taken together, these results suggest a PCD-triggering mechanism in which H2O2 first inactivates a carbonyl reductase(s), allowing RCS levels to rise, and eventually leads to the activation of the C3LP activity of 20S proteasome. The carbonyl reductase thus acts as an ROS sensor for triggering PCD.